Coleção Etnobotânica - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2025)
In this volume you will discover the ethnobotanical collection, composed of plant drugs, various artifacts, and plant raw materials used in the production of products and artifacts.
Ethnobotanical Collection
Keywords: Plantas; Povos tradicionais; Artefatos; Vegetais - Matéria Prima; CIENCIAS BIOLOGICAS::BOTANICA